(untitled) (Italiano LinguaDue, 2025)
Il lavoro si sofferma sullo spazio e sul ruolo assegnato ai linguaggi specialistici nella didattica della lingua italiana, con riferimento a esperienze di didattica universitaria condotte in Italia (si dà anche conto della presenza e della distribuzione di corsi e insegnamenti dedicati, nel contesto della L1 e della L2/LS). Si offrono poi spunti per un’ipotesi di progettazione didattica dell’italiano specialistico L1 pensata per un corso universitario di secondo livello di ambito non linguistico-letterario e non umanistico. The L1 specialist Italian in university as a professionalizing Italian (with ideas for a didactic proposal between rewriting and IA) The work focuses on the space and role assigned to specialist languages in the teaching of the Italian language, with reference to university teaching experiences conducted in Italy (The presence and distribution of courses and teaching in the context of L1 and L2/LS is also taken into account). It is then presented a hypothesis of didactic design of the specialized Italian L1 designed for a university course of second level of non-linguistic-literary and non-humanistic scope.